Native tourism, natural forests and local incomes on Ilha Grande, Brazil - Wunder, Sven (Edward Elgar Publishing, 2003)
Tourism on Ilha Grande is to an overwhelming extent nature-based and the attractiveness of the island as a tourist destination is neatly linked to its extensive forest coverage. At about 150 km from Rio de Janeiro and 400 km from São Paulo, Ilha Grande is close to two of the most populous cities in the southern hemisphere. It thus caters predominantly to native Brazilian tourists. Looking specifically at local incomes from low-income tourism in the case of the traditional fishermen’s village of Aventureiro, the hypothesis that ‘backpackers leave no money on the island’ was clearly rejected. Campers spend little per capita, but their large numbers generate sizeable incomes. The discourse of the tourism planners on Ilha Grande generally was about environmental carrying capacity – ‘degradation of the environment’ – yet the substance behind it is actually about perceptional limits. Has perceptional carrying capacity objectively been surpassed? Obviously not, since limits are subjective and differ enormously between, on the one hand, the low-spending students – and the camping ground owners catering to them – and, on the other, the higher middle-class tourist – and the up-market hostel owners with considerable investments at stake. The study concludes that native tourism can have significant positive spin-offs on both livelihoods and environmental conservation, but considerable trade-offs between tourism types and stakeholder interests can develop over the life cycle of a tourism destination, paving the way for struggles around the political economy of tourism.